Effects of mutant lamins on nucleo-cytoskeletal coupling in Drosophila models of LMNA muscular dystrophy - Shaw, Nicholas M.; Rios-Monterrosa, Jose L.; Fedorchak, Gregory R.; Ketterer, Margaret R.; Coombs, Gary S.; Lammerding, Jan; Wallrath, Lori L. (Frontiers in Cell and Developmental Biology, 2022)
The nuclei of multinucleated skeletal muscles experience substantial external force during development and muscle contraction. Protection from such forces is partly provided by lamins, intermediate filaments that form a scaffold lining the inner nuclear membrane. Lamins play a myriad of roles, including maintenance of nuclear shape and stability, mediation of nuclear mechanoresponses, and nucleo-cytoskeletal coupling. Here, we investigate how disease-causing mutant lamins alter myonuclear properties in response to mechanical force. This was accomplished through a novel application of a micropipette harpooning assay applied to larval body wall muscles of Drosophila models of lamin-associated muscular dystrophy. The assay allows measuring both nuclear deformability and intracellular force transmission between the cytoskeleton and nuclear interior in intact muscle fibers. Our studies revealed that specific mutant lamins increase nuclear deformability while other mutant lamins caused nucleo-cytoskeletal coupling defects, which was associated with loss of microtubular nuclear caging. We found that microtubule caging of the nucleus depended on Msp300, a KASH domain protein that is a component of the Linker of Cytoskeleton and Nucleoskeleton (LINC) complex. Taken together, these findings identified residues in lamins required for connecting the nucleus to the cytoskeleton and suggest that not all muscle disease-causing mutant lamins produce similar defects in subcellular mechanics.